2019
DOI: 10.1111/ijpo.12532
|View full text |Cite
|
Sign up to set email alerts
|

Association between overweight or obesity and the risk for childhood asthma and wheeze: An updated meta‐analysis on 18 articles and 73 252 children

Abstract: Background: Overweight or obesity is increasingly recognized as a possible risk factor for childhood asthma. Objectives:We aimed to meta-analyse the association between overweight or obesity and the risk for childhood asthma and wheeze and meanwhile explore potential causes of between-study heterogeneity.Methods: Literature search, study selection, and data extraction were performed independently and in duplicate. Data were analysed by STATA software.Results: Eighteen articles and 73 252 children were analysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 45 publications
(97 reference statements)
1
63
0
6
Order By: Relevance
“…Another meta-analysis with 13 studies showed a positive correlation with 1.47 odds ratio between abdominal obesity and asthma [66]. Taken together, these studies have suggested that a higher prevalence of asthma is observed among obese and overweight adults and children, who are also at risk of increased severity and a worse prognosis [39,[63][64][65][66][67]. However, precise mechanism of obesity causing asthma in children are still not clear, while late-onset asthma is mostly neutrophil-predominant and non-IgE-mediated, which shows increased levels in adipokines [68].…”
Section: Obesity and Allergymentioning
confidence: 90%
See 1 more Smart Citation
“…Another meta-analysis with 13 studies showed a positive correlation with 1.47 odds ratio between abdominal obesity and asthma [66]. Taken together, these studies have suggested that a higher prevalence of asthma is observed among obese and overweight adults and children, who are also at risk of increased severity and a worse prognosis [39,[63][64][65][66][67]. However, precise mechanism of obesity causing asthma in children are still not clear, while late-onset asthma is mostly neutrophil-predominant and non-IgE-mediated, which shows increased levels in adipokines [68].…”
Section: Obesity and Allergymentioning
confidence: 90%
“…In adult study, 9,888 Japanese subjects study reported that obese significantly increases a risk of late-onset asthma only in women [64]. Meta-analysis of 18 children-subjected articles revealed that overweight or obese showed 1.30-fold increase in a risk of childhood asthma, and 1.90 for wheeze [65]. Another meta-analysis with 13 studies showed a positive correlation with 1.47 odds ratio between abdominal obesity and asthma [66].…”
Section: Obesity and Allergymentioning
confidence: 98%
“…Thirdly, in this meta-analysis, the categorization of asthma, such as ever, current, and persistent asthma was lack. Fourthly, some, but not all included studies had adjusted for child's weight or BMI at the time of assessment, indicating that the effect of maternal obesity on asthma and wheeze is not independent of childhood obesity, which is an established risk factor for asthma and wheeze (46).…”
Section: Discussionmentioning
confidence: 99%
“…Obese children often have dyspnea and other respiratory problems, but these are not always due to asthma. Overweight and obesity in children is a clear risk factor for bronchial asthma, especially in girls [ 1 , 4 ]. When obese children develop asthma, they have a more severe disease phenotype associated with a higher burden of disease, reduced quality of life, greater frequency of exacerbations and hospitalization, and a suboptimal response to commonly used asthma medicines [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%